PENGARUH KEPEMIMPINAN DAN EFIKASI DIRI TERHADAP INOVASI DALAM BERWIRAUSAHA PASCA PANDEMI COVID-19 PADA SEKTOR EKONOMI KREATIF DI KOTA MEDAN - Diza Rahmi Puteri Rahayu; Marliyah Marliyah; Rahmat Daim Harahap (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2022)
The creative industry is an industry that originates from the utilization of individual skills, creativity and talents in creating wealth and employment opportunities that focus on empowering creativity and creation. This study aims to determine the effect of leadership and self-efficacy on innovation in entrepreneurship after the Covid-19 pandemic in the creative economy sector in the city of Medan. The research method used is quantitative research with a descriptive approach. Data collection technique is by distributing questionnaires to respondents and observation. The results of the study show that leadership and self-efficacy have a positive and significant effect on innovation in entrepreneurship after the Covid-19 pandemic in the creative economy sector in Medan City.